Work adjustments for patients with hemophilia - Negin Kassiri; Samaneh Seydi Joughan; Hossein Shabani (Health Science Monitor)
Background: Hemophilia is a bleeding disorder which is inherited in an X-linked recessive pattern. A person with hemophilia is unable to stop the bleeding process due to the low level or absence of coagulation factors. This may lead to spontaneous bleeding as well as bleeding following injuries or surgical procedures. Case presentation: In this study, we investigated work adjustments in two cases of patients with hemophilia A. Conclusion: Work adjustments depend on the severity of the disorder. Patients with mild hemophilia can work normally in any job, but those with a high risk of bleeding may have some restrictions.